Gamificando as operações de Ground handling para aumento da segurança no aeroporto do Recife. - Silva, Leonardo Savio L. S. da (2021)
Ground Handling (GH) is defined as the services provided on the airport floor related to the handling of aircraft from their landing until their next takeoff. According to the 2019 annual report of ANAC (National Civil Aviation Agency), there was a growth of 1.35% in passenger transport compared to 2018, resulting in a number of 104.4 million passengers served by companies Brazilian airlines in 2019. This increase brought a great challenge on the safety of people and equipment involved in these services. However, the low engagement and lack of adherence by the teams regarding the correct execution of operational procedures in compliance with safety standards is still a problem in these operations. In this work, we will use a gamification strategy applied to ground handling processes in aircraft service with the aim of generating more engagement and understanding of the importance of safety practices. For this purpose, contributions on gamification applied to the corporate world were used, as was the case with McGonigal (2011), Dubey (2017) and Vianna et al. (2013), adding research in the context of safety culture in operations with Balk (2007), Duplin (2015) and Bieder (2018). We applied the Gamification Canvas (VIANNA et al., 2013) to engage the increased reporting of situations below safety standards by people, and also to ensure proper learning based on these minor risks incidents, and doing so, real accidents can be avoided. This work contributes to the field of communication and the generation of a culture of safety in companies in the context of corporate governance, while demonstrating the application of creative industry processes in an efficient manner with regard to practices that prevent accidents.